Bacteriological Profile and Antibiotic Sensitivity Patterns in Children with Urinary Tract Infection: A Cross-Sectional Study in the Northern Part of Bangladesh (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: urinary tract infection children bacteriological profile antibiotic sensitivity